Enhanced Crack Resistance of Porous Anodic Aluminum Oxide Grown on a Tubular Substrate with the Additive Ethylene Glycol - Sianturi, Manogari; Juwono, Ariadne Laksmidevi; Anawati, Anawati (UI Scholars Hub, 2025)
The growth of a porous anodic aluminum oxide (PAAO) layer with fewer cracks on a tubular substrate is quite challenging. The PAAO layer on a curved surface grows slower than that on a flat surface and is susceptible to cracking. This study aims to improve the crack resistance of the PAAO layer grown on a tubular aluminum substrate by adding ethylene glycol (EG). Each bath contained additive concentrations of 0, 5, 10, and 15 vol% EG. Anodization proceeded for 4 h at a temperature of 10 ℃ using the potentiostatic mode at 25 V in a sulfuric acid bath and 40 V in an oxalic acid bath. The crack and pore structure were investigated using a field emission scanning electron microscope (FE-SEM). The kinetic curve and FE-SEM investigation indicated that the addition of EG in the bath slowed the growth rate of the PAAO layer in both anodization baths. The lower oxidation rate drastically improved the crack resistance, as revealed by the significant reduction in the crack population and narrower crack width. The additive EG presumably enhanced the electrolyte viscosity and reduced the heating effect released during oxide growth. Consequently, the layer thickness and pore size decreased with the increase in the EG concentration.